A Pivotal Moment for Guyana : Realizing the Opportunities - World Bank (World Bank, Washington, DC, 2021)
Guyana stands at the threshold of a new era. The recent discovery of vast offshore oil and gas (O&G) reserves and the start of production, is poised to fundamentally transform the structure of the Guyanese economy while generating an influx of fiscal revenue. Prior to the discovery, extractive industries and commodity exports already played a major role in Guyana’s economy and public finances. However, the mining sector created few jobs and had a limited impact on poverty reduction. The rise of the O&G sector poses unprecedented macro-fiscal management challenges while offering new opportunities to address longstanding development constraints. The development of oil-producing countries often comes at high cost of environment and climate change, which needs to be balanced. In addition, the country is now facing the challenges from the COVID-19 pandemic that will stretch the public health systems and highlight inadequacies of testing and treatment facilities. The SCD is organized into six chapters. Chapter 1 situates the development of the oil sector within Guyana’s broader economic, social, and political context. Chapter 2 estimates the magnitude of fiscal revenues from the oil sector, along with alternative cost scenarios, and the implications of alternative strategies for allocating these revenues and considers how policies can mitigate the macro-fiscal and environmental risks posed by the sector. Chapter 3 focuses on institutional quality and good governance, especially in terms of strengthening the public sector, and it details challenges related to the design and implementation of a sovereign wealth fund, which the international experience has shown to be vital to the success of resource-rich developing countries. Chapter 4 explores how the government can leverage natural resource revenues to accelerate Guyana’s economic transformation and spur job creation. Chapter 5 evaluates strategies for transforming Guyana’s natural capital into human capital and reaching full coverage of basic services and infrastructure through investment in health, education, and social protection. The chapter highlights the constraints in human capital development and health facilities; even more critical that these are addressed in context of the current COVID-19 pandemic. Chapter 6 prioritizes interventions necessary to generate enduring gains in poverty reduction and shared prosperity. A key offering of the chapter is a spatial development package to address deficiencies in basic service delivery and infrastructure necessary to protect well-being and health of Guyanese citizens. To ground the analysis in the real-world experience of Guyanese communities, each chapter begins with a brief discussion of how the newfound wealth will affect the most vulnerable and marginalized households.